A comprehensive review on nanotechnology application in wastewater treatment a case study of metal-based using green synthesis - Sikiru, S. (Elsevier Ltd, 2022)
In nanotechnology, the green synthesis of nanoparticles (NPs) is a new research trend in science and engineering because it is nontoxic or less hazardous, eco-friendly, efficient, and cost-effective when compared to other traditional physical and chemical approaches. Plant-based green synthesis of NPs utilizes a variety of biological agents such as plants, bacteria, algae, and fungus, but plant-based green synthesis of NPs is gaining popularity among researchers worldwide. Because of their great efficiency and biocompatibility, a variety of green-produced NPs are now being employed in water and wastewater treatment. Green produced NPs are extremely effective in recycling and removing heavy metals from wastewater. However, the shortage of water across the globe is probable to create a global water crisis. Surface water reliance seems to be insufficient to solve the rising in water demand, more also the increase in industrialization, urbanization, agriculture practices, social and environmental problems have caused generation of wastewater which have made the water to be polluted and contaminated. In this review the overview of water treatment techniques most especially the used of green synthesis application such iron nanoparticles are discussed in details, heavy metal removal which are threat to human life such as Zn, Cu, Hg, and Pb that are needed to be removed from the food chain, adsorption Isotherms, and Kinetics behavior, wastewater purification, removal of contaminants from wastewater, wastewater treatment processing, influence of nanotechnology in treatment of water, water purification process, and importance of nanomaterials in treatment of water purification are well elucidated. Moreover, this review also highlights the prospect of nanoparticles in the treatment of water. Â© 2022 Elsevier Ltd. All rights reserved.